'The Nature of the Question Demands a Separation': Frege on Distinguishing between Content and Force. Issue 2 (3rd April 2021) - Textor, Mark
ABSTRACT: Recently, the content/force distinction has had a bad press. It has been argued that the distinction is not properly motivated and that it makes the problem of the unity of the proposition intractable. I will argue that Frege's version of the content/force distinction is immune from these objections. In order to do so, I will reconstruct his argument that 'the nature of a question' requires a distinction between force and content. I will answer the concern about the unity of the proposition by outlining how the distinction can be combined with a Fregean account of the unity of thought.